The Poverty in Indonesia: Concept, Approach, and the Reduction Strategies - Musiyam, Muhammad (Forum Geografi, 1991)
Apparently, the policy of raise poverly in Indonesia start to change. In PJPT I, the strategy to raise the poverly acupied the position âSide stream of developmentâ only. That is, the effort to raise the poverly only applied the components of macro economic policy to maintain the growth of the economy in high position. In PJPT II this effort occupy the position âmain stream of developmentâ. That is, not only does the effort depend on âtrickle down effectâ, but also through direct attack that concern to destitude people. The poverly phenomenon is complex problem and multidimensional, thatâs not merely concern with welfare aspect (materially). Therefore, in order to the raising of poverly run effectively, we have to look the dimension of poverly as a whole. Complexity of poverly problems vary from place to place. Therefore, it is needed an accurate strategy and it must consider the characteristic of poverly and the potency that suitable to be developed.Â